1971
DOI: 10.1128/jb.108.2.668-679.1971
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Synthesis in Bacillus subtilis During Development of the Competent State

Abstract: Rates of deoxyribonucleic acid, ribonucleic acid, and protein synthesis were examined in purified competent cells of Bacillus subtilis during the development of the transformable state. To become competent, a cell must depart from the normal course of vegetative growth and pass through a precompetent phase beginning as early as 90 to 180 min before the appearance of transformability. While in the precompetent state, the cell decreases its rate of deoxyribonucleic acid synthesis and lowers its ratio of ribonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 14 publications
4
26
0
Order By: Relevance
“…Not only are cell division and elongation arrested, but DNA replication also appears to be blocked, as the nuclear bodies of competent cells retain the appearance of resting nucleoids. It has been reported that DNA replication and stable RNA synthesis are blocked in the presumptive competent cells during the development of competence (Dooley et al, 1971) and in newly transformed cells (McCarthy and Nester, 1967). The present results confirm that the inhibition of DNA replication continues during outgrowth.…”
Section: Discussionsupporting
confidence: 88%
“…Not only are cell division and elongation arrested, but DNA replication also appears to be blocked, as the nuclear bodies of competent cells retain the appearance of resting nucleoids. It has been reported that DNA replication and stable RNA synthesis are blocked in the presumptive competent cells during the development of competence (Dooley et al, 1971) and in newly transformed cells (McCarthy and Nester, 1967). The present results confirm that the inhibition of DNA replication continues during outgrowth.…”
Section: Discussionsupporting
confidence: 88%
“…The most suggestive comparison may be with a recent report that when the initiation of chromosome replication is specifically blocked in E. coli, cells become elongated, with centrally located nucleoids (Bernander et aL, 1995). mecA inactivation may be responsible for the DNA replication arrest of competent cells It has been shown that competent cells of B. subtilis are essentially inactive with respect to DNA replication (Dooley et aL, 1971;Dubnau and Cirigliano, 1973), and that chromosome replication in these cells is arrested at or near the replication terminus (McCarthy and Nester, 1967). Reversal of this block occurs with a delay, resulting in a prolonged lag before competent cells resume growth (McCarthy and Nester, 1967;Nester and Stocker, 1963).…”
Section: Inappropriate Comk Synthesis Causes An Abnormality In Nucleosupporting
confidence: 57%
“…These cells are physiologically distinct; they are more buoyant than the non-competent cells and can be separated from the latter on density gradients (Hadden and Nester, 1968;Haseltine-Cahn and Fox, 1968). Additionally, they are blocked in DNA replication (Dooley et aL, 1971;Dubnau and Cirigliano, 1973), and when resuspended in fresh medium, exhibit a prolonged lag period before the resumption of growth (Nester and Stocker, 1963). As in the case of other globally regulated states, especially those that can arrest growth, such as sporulation, SOS and heat shock, a mechanism must exist to return the system to the uninduced state (Neihardt, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Competence and sporulation may be viewed as the penultimate and ultimate responses to stress. They must be tightly regulated, probably because competent and sporulating cells are non-dividing (Dooley et al, 1971;B. J. Haijema, J. Hahn, D. Dubnau, unpublished observations).…”
Section: Introductionmentioning
confidence: 99%